Shoe Wash Service Business Management in MSMEs (Karanganyar Shoes and Care Case Study) - Ardianto, Alfian; Suyatmini, S (Proceedings International Conference on Education Innovation and Social Science, 2025)
Shoes in addition to functioning as foot protectors are also part of lifestyle and appearance support, so shoe care is an important aspect for most people, especially the younger generation who are aware of cleanliness and aesthetics. From this phenomenon emerged a business opportunity that is quitepotential, namelyshoewashing services. In thisstudy, it aims to describe and analyze the management of the shoe washing service business in MSMEs with a case study at Shoes and Care Karanganyar. The focus of this research is directed at three main aspects, namely planning, implementation, and improving service quality. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that Shoes and Care Karanganyar has implemented systematic business planning by showing operational standards, market segmentation, and resource readiness. The implementation of services is carried out through structured stages, starting from the receipt of shoes, the washing process, drying and finishing, to returning to customers.in addition, service quality improvement continues to be carried out through monthly evaluations, HR training, and the implementation of service innovations.